Dynamic simulation of the wireline riser tensioner system for a mobile offshore drilling unit based on multibody system dynamics. (15th September 2015) - Lee, Hyewon; Roh, Myung-Il; Ham, Seung-Ho; Ha, Sol
Abstract: In this study, a wireline riser tensioner (WRT) system was dynamically simulated to analyze the dynamic response of the riser string in a mobile offshore drilling unit (MODU) such as a drilling rig or a drillship. The main function of the WRT system is to sustain the tension to avoid buckling, regardless of the MODU motion. The WRT system consists of a tensioner ring, a wireline, pneumatic cylinders, and air pressure vessels (APVs). It reduces the vertical (heave) motion of the top of the riser string caused by the MODU motion. In this study, the equations of motion of the drilling rig and the WRT system were formulated based on multibody system dynamics. The discrete Euler–Lagrange equation was used to formulate the equations of motion. For the external forces, both the hydrostatic and hydrodynamic forces were considered. Several simulations were performed with various sea states to analyze the motion of the riser string and the efficiency of the WRT system. Furthermore, the gas volume inside the APVs was changed to investigate its impact on the efficiency and performance of the WRT system. Highlights: We model a drilling rig with the riser string and the wireline riser tensioner (WRT) system as a multibody system. The equations of motion are formulated using the discrete Euler–Lagrange equation. We analyze the tension acting on the riser string considering various operating conditions. The gas volume of the WRT system is changed to investigate its impact on the system.